2022
DOI: 10.4143/crt.2021.575
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Ocular Surface Disorders and Retinopathy: Ocular Structures and Radiation Dose-Volume Effect

Abstract: To evaluate the radiation induced adverse effects on ocular structures in head and neck cancer patients and investigate the radiation dose-volume effects on the cornea, lacrimal gland, retina, optic nerve and chiasm. Materials and MethodsA total of 38 eyes of 19 patients were included in this prospective, cohort study. All patients underwent complete ophthalmological examination in addition to contrast sensitivity, visual field and visual evoked potentials (VEP) tests. Ophthalmological examinations and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
(29 reference statements)
0
7
0
1
Order By: Relevance
“…3,4 The microvascular alterations are associated with a reduction of retinal oxygenation, blood flow, and ischemia. [2][3][4] Contrast sensitivity decrease and visual field impairment were notified in patients treated with radiotherapy. 1 Our patient had gradually decreased bilateral visual acuity, as well as cataract and optic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 The microvascular alterations are associated with a reduction of retinal oxygenation, blood flow, and ischemia. [2][3][4] Contrast sensitivity decrease and visual field impairment were notified in patients treated with radiotherapy. 1 Our patient had gradually decreased bilateral visual acuity, as well as cataract and optic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…1 The proximity with orbit tissues exposes them to severe damages. 2 However, late-onset, sight-threatening ocular complications may occur, including cataract, optic neuropathy, radiation retinopathy (RR), and ocular surface disease. 2 The early diagnosis of these lesions allowed to better prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Forest plot of studies that reported radiation-induced retinopathy events [ 1 , 7 , 21 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 42 , 44 , 45 , 46 , 47 , 48 , 49 ]. …”
Section: Figurementioning
confidence: 99%
“…[14] Radyasyon retinopati sıklıkla radyasyon keratopatisi, katarakt ve radyasyon optik nöropatisi gibi radyoterapinin diğer oküler komplikasyonları ile birlikte bulunabilir. [15,16]…”
Section: Introductionunclassified